Tobacco use by pregnant Medicaid beneficiaries: Validating a claims-based measure in Oregon - Luck, Jeff; Larson, Anne E.; Tong, Van T.; Yoon, Jangho; Oakley, Lisa P.; Harvey, S. Marie (Preventive medicine reports, 2020)
•Medicaid claims data for maternal smoking are in agreement with birth certificates.•Sensitivity of claims data varied by some maternal characteristics.•Medicaid claims may offer a valid tool for timely surveillance of maternal smoking. In Oregon, more than 4 in 5 pregnant women who smoke are covered by Medicaid. Although birth certificate data for smoking during pregnancy are not accessible in a timely manner, Medicaid claims data are available monthly and provide person-level data. This study utilized an individually linked database of Medicaid claims and birth certificate data to compare the prevalence of tobacco use diagnosis codes in Medicaid claims data to self-reported smoking during pregnancy reported on birth certificates. We computed the sensitivity and specificity of Medicaid claims data to ascertain tobacco use during pregnancy compared to self-report on linked birth certificates. Using logistic regression models, we also examined demographic, prenatal care, and behavioral health factors that predicted agreement between claims and birth certificates. From 2008 to 2013, 17.9% of women with Medicaid births reported smoking during pregnancy on birth certificates compared to 3.8% of non-Medicaid births. Tobacco-related claims during pregnancy were present for 12.6% of Medicaid births. Overall agreement between claims and birth certificates rose from 87.0% in 2008 to 90.2% in 2013; sensitivity rose from 43.0% to 62.2%. Sensitivity was lowest for Hispanic women and highest for White women, and declined as maternal education increased. Sensitivity was 33.9 percentage points higher for women with any mental illness diagnosis and 27.3 percentage points higher for women with any substance use disorder diagnosis. Specificity was greater than 95% in all years. Medicaid claims data may help in surveillance of maternal smoking rates and assessment of smoking cessation programs for female Medicaid beneficiaries of reproductive age.